Do higher summer temperatures restrict the dissemination of Hymenoscyphus fraxineus in France?. Issue 4 (13th March 2018) - Grosdidier, M.; Ioos, R.; Marçais, B.
Summary: Hymenoscyphus fraxineus is an invasive pathogen that severely affects European ashes, jeopardizing the use of this species in forestry. However, even aggressive invasive pathogens require environmental conditions conducive to disease development. Hence, H. fraxineus survival at temperatures above 35°C is limited, which could reduce its impact in southern Europe. This study examined the effect of environmental conditions, mainly summer temperatures, on ash dieback development in southeast France between 2015 and 2016. Fourteen sites were selected according to altitudinal and longitudinal gradients covering a wide range of mean summer temperatures. Disease severity, density of infected and healthy rachises in the litter and quantity of apothecia produced on infected rachises were measured. Results point to limited disease severity in this area because of the occurrence of high summer temperatures that are unfavourable to the pathogen. In a context of global warming, increases in temperatures could have a positive impact on ashes by limiting ash dieback development.